Senegal : Enhanced Heavily Indebted Poor Countries (HIPC) Initiative Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines the completion point document for Senegal's Enhanced Initiative for Heavily Indebted Poor Countries. Senegal could reach the completion point on the basis of a full poverty reduction strategy and sound macroeconomic policies, as well as specific structural and social reforms set out in the decision point document. Major reforms have been advancing in the energy and groundnut sectors and in the postal and pension systems, and institutional improvements in public financial management toward better controls and transparency have been made and are continuing.